Synthesis of 2,2′-Bipyridines via Dehydrogenative Dimerization of Pyridines Using Sodium Dispersion - De, Pinaki Bhusan; Ilies, Laurean; Takai, Kazuhiko; Asako, Sobi (Synlett, 2023)
2,2′-Bipyridine derivatives were synthesized by dehydrogenative dimerization of nonactivated pyridines using sodium dispersion. The reaction features operational simplicity, mild conditions, and the use of earth abundant and nontoxic sodium as the sole metal source. Importantly, transition metals are not required, which is beneficial in the fields of materials science and drug synthesis, where the contamination of the transition metals may cause significant problems.
Keywords: 2,2′-bipyridine; sodium dispersion; dehydrogenative coupling; transition-metal-free; sustainable chemistry